Near crushing mechanism of gangue-containing coal seams and parameter optimization for combined fully mechanized caving - Hao, Xiaobo; Liu, Pengcheng; Deng, Yanhui; Chi, Xiaolou; Li, Zhihua (Frontiers in Earth Science, 2023)
Fully mechanized caving is the most popular method for safe and efficient coal mining in our China. In this study, based on geological and mining conditions of Workface 822 of the Yuandian No. 1 Mine, we used theoretical analysis and numerical simulation to analyze the crushing mechanism of gangue-containing coal seam roofs, discuss the mechanical model of stability of gangue-containing coal seams to simulate different methods and caving intervals, and optimize the caving parameters of coal from gangue-containing coal seams. The results indicate that under the action of mining-induced stress, the peak pressure on the support is less than the rupture stress of the gangue, and relying on the mine support pressure alone can promote the rupture of the roof coal. However, it is difficult to rupture the gangue in the roof; owing to the gangue-containing coal seams, the area where the damage coefficient of the roof coal at the upper end of the support is lower than one is further expanded from the front of the support to the entire upper area of the support, and the crushing effect of roof coal is greatly weakened. After comparing the effects of the five caving modes, we finally decided to use the single-cycle interval caving mode. The minimum gangue content of Workface 822 of the Yuandian No. 1 Mine is 54.35%. The results of this study can provide a theoretical basis and experience-based reference for the safe and efficient mining of gangue-containing coal seams.